(untitled) (Sains Humanika, 2024)
The flow state is a mental state in which a person is fully immersed in an activity and experiences a sense of energized focus, full involvement, and enjoyment. It is a highly desirable state for learning, as it allows students to be more engaged and productive. However, achieving the flow state can be challenging, and there is no single method guaranteed to achieve all the conditions of this state. Additionally, this study argues that achieving the flow state is advantageous in STEAM education because it has the potential to increase student engagement and motivation, improve learning outcomes, promote creativity and problem-solving skills, and develop 21st-century skills such as collaboration and critical thinking. Therefore, this study aims to develop a new framework for achieving the flow state in STEAM education by investigating the implementation of a combined approach using impactful technology (ITU) and gamification (IGU). The framework combines impactful technology use (ITU) and impactful gamification use (IGU) to create activities that are challenging, have clear goals, provide immediate feedback, and promote action-awareness merging. A concurrent triangulation mixed-methodology research design was used, with data collected from teachers, students, and parents through questionnaires, interviews, and observations. The researcher used purposive sampling to determine the sample, which consisted of eighty-nine teachers, ten students, ten parents, and ten lesson observations. The study is significant because it is the first to propose a new model for achieving the flow state in STEAM education. The findings were used to develop the New Combined Flow Framework (NCFF), which supports achieving the conditions for the flow state in STEAM learning through the combined use of ITU and IGU. This new framework can be used by education professionals to practically achieve the flow state in STEAM classes. By understanding how to achieve the flow state, educators can create more engaging and effective learning experiences for their students, potentially revolutionizing STEAM education and making it more accessible to all students.